Identifying risk factors affecting exercise behavior among overweight or obese individuals in China - Shengyu, Guo; Liu, Feiyue; Wu, Qinghua (Frontiers in Public Health, 2023)
Background The disease burden caused by obesity has increased significantly in China. Less than 30% of those obesity met the weekly physical activity standards recommended by WHO. Risk factors that influence exercise behavior of obesity remains unclear. Methods Based on the survey from the Chinese General Social Survey program (CGSS) in 2017, 3331 subjects were identified and enrolled in univariate and multiple probit regression model, we intend to identify the association between SRH and exercise behavior of those obesity, and further to explore Influencing factors of active physical activity in obese people. Results The proportion of active physical activity in obese people was 25%. Groups with better SRH, higher education and income were more likely to participate in sports. Obesity who lived in rural areas, unmarried or divorced or and were 35-40 years old had a significantly lower percentage of active physical activity. Conclusions The proportion of obesity who meeting the recommendation of physical activity (WHO) in China was not optimistic. Health promotion programs for those obesity need to be further strengthened and targeted, especially for rural areas, low-income families and middle-aged obese people.